A novel design for hardware interface board with reduced resource utilization - G. S. Ananth; N. Shylashree; Satish Tunga; Latha B. N. (Indonesian Journal of Electrical Engineering and Computer Science, 2021)
The final cost of an integrated circuit (IC) is proportional to its testing time. One of the main goals of test engineers when building an IC test solution is to reduce test time. Reduction of Test time is achieved by multi-site testing where multiple ICs are tested simultaneously using automated test equipment (ATE). During multi-site testing, if a certain test requires abundant resources, it is accomplished by testing one set of ICs at a time while the other ICs remain idle, thus lengthening the total test time. In digital-analog hybrid ICs, both analog and digital tests need to be performed, increasing the tester resource requirement and causing digital resource shortage. This paper describes a hardware interface board (HIB) design for a test case of a digital-analog IC on Teradyne’s ETS-364 ATE. The HIB's design allows the ATE to perform multi-site I2C based tests, which usually require lot of tester resources, utilizing only two digital resources and one measurement resource. This design achieves halving the I2C test time while lowering the number of resources necessary for multi-site testing compared to set-by-set testing. The proposed work has achieved up to 90.625% of resource reduction for multisite testing for a single test.